(3GdJUOjbIs
(3ChdgG (B:s
(3HYO GdHSedI (B: (3JUOjbI UOb Gddg GdYXje GdbGOQ GdebJOQ GdYdi GdLdjd GdbOQ adGRhGd dedcg hdG JMhd abGd TYQ jG HOQ HGOQ Edi HGdcGS aQH NjQ CJi Ydi HGSi s
(3BNQgG (B:s
(3hbGd ZjQg (B: (3JGddg dG CfSi YghO ehOJi MJi GdeeGJ hdG CMhd Yf GdhaG bO PHJ ef Cde Gdfhi HUHGHI dh jHJdi HOQ GdJeGe HgG GNJai s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B190 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2328) s
Keywords: (3GdCOHs